Effect of exposure to ultraviolet-activated oxygen on the electrical characteristics of amorphous indium gallium zinc oxide thin film transistors - Liu, P. (2013)
An exposure of the back channel of an indium gallium zinc oxide (IGZO) thin film transistor (TFT) to ultraviolet (UV)-activated oxygen can effectively shift the threshold voltage (Vth) of the TFT. The Vth decreases linearly with the exposure time while the on-state current greatly increase with the exposure time. The exposure doesn't have a strong impact on other device parameters. The effect of the exposure on the Vth is attributed to the increase in the electron concentration of the channel layer as a result of the creation of oxygen vacancies by exposure.